Evaluation of Primary Central Incisors Requiring Restoration and Pulpectomy in 2 to 6 Year Old Children-An Observational Study - Pavithiraa Sankar, Vignesh Ravindran (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the first teeth to get affected by early childhood caries are the primary central incisors therebyesthetics is a main concern in restorations related to primary anterior teeth. In this study the severity ofcarious lesions are identified by the type of treatment performed. It is a retrospective study analyzing theneed for a restoration as compared to a pulp therapy in primary central teeth. This is a private hospital basedretrospective study. This is a hospital based retrospective study. All data of the patients visiting SaveethaDental College and hospitals from June 2019 to March 2020 located in Chennai were retrieved manually.Children who were diagnosed with early childhood caries between 2-6 years who had caries in at least oneof the primary central incisors (51, 61 ,71, 82) indicated for restorations or pulpectomy were included. Atotal of 832 teeth were treated out of which 476 were of males (57.21%) and 356 were of females (43.89%).The highest number of treatment procedures was done in 3-4 year olds – 244 procedures (58.53%). The mostcommonly treated tooth was primary maxillary left central incisor – 389 procedures (45.67%). Only 31.25%of the teeth underwent pulpectomy procedures. We can conclude restorations were performed in 3-4 year oldcommon among male children in the primary maxillary left central incisor when compared to pulpectomy.